Visual inspection on premature failure of electric motor bearings - Edy Sutjipto, Agus Geter; Triwiyanto, A; Aminanda, Yulfian; Fekry Faris, Waleed; Adesta, Erry Yulian Triblas (Trans Tech Publications, Switzerland, 2011)
All electrical motor or generator bearings can potential suffers from electric erosion. Unfortunately, problems can start after just a few months of running a new electric motor or generator. From visual inspection, it was found that the failure happened on the raceway surface in equal spacing. There may be many reasons for this – heavier loading than has been anticipated, inadequate or unsuitable lubrication, careless handling, ineffective sealing, or fits that are too tight, with resultant insufficient internal bearing clearance. Each of these factors produces its own particular type of damage and leaves its own special imprint on the bearing. Consequently, by examining a damaged bearing such as visual inspection, it is possible, in the majority of cases, to form an opinion on the cause of the damage and to take the requisite action to prevent a recurrence